TI_GERICHTE 11.2020.6 vom 20. Juli 2021 , Scioglimento di comproprietà immobiliare e modo della divisione prima del divorzio - TI Tribunale d'appello (2021)
Scioglimento di comproprietà immobiliare e modo della divisione prima del divorzio